Speech technologies - recognition and analytics - Wax, Jonathan (Henry Stewart Talks, 2009)
Contact center challenges, Speech: the options, Current deployments, Technology, Applications, Contact center analytics, Elements of a sustainable solution, Call driver analysis, Customer success stories